Detailed characterization of tumor infiltrating lymphocytes in two distinct human solid malignancies show phenotypic similarities. Issue 1 (18th November 2014) - Kovacsovics-Bankowski, Magdalena; Chisholm, Lana; Vercellini, Jonna; Tucker, Christopher G; Montler, Ryan; Haley, Daniel; Newell, Philippa; Ma, Jun; Tseng, Paul; Wolf, Ronald; Vetto, John T; Hammill, Chet; et al.
Abstract : Background: We examined the phenotype and function of lymphocytes collected from the peripheral blood (PBL) and tumor (TIL) of patients with two different solid malignancies: colorectal cancer liver metastases (CRLM) and ovarian cancer (OVC). Methods: Tumor and corresponding peripheral blood were collected from 16 CRLM and 22 OVC patients; immediately following resection they were processed and analyzed using a multi-color flow cytometry panel. Cytokine mRNA from purified PBL and TIL CD4 + T cells were also analyzed by qPCR. Results: Overall, we found similar changes in the phenotypic and cytokine profiles when the TIL were compared to PBL from patients with two different malignancies. The percentage of Treg (CD4 + /CD25 + /FoxP3 + ) in PBL and TIL was similar: 8.1% versus 10.2%, respectively in CRLM patients. However, the frequency of Treg in primary OVC TIL was higher than PBL: 19.2% versus 4.5% (p <0.0001). A subpopulation of Treg expressing HLA-DR was markedly increased in TIL compared to PBL in both tumor types, CRLM: 69.0% versus 31.7% (p = 0.0002) and OVC 74.6% versus 37.0% (p <0.0001), which suggested preferential Treg activation within the tumor. The cytokine mRNA profile showed that IL-6, a cytokine known for its immunosuppressive properties through STAT3 upregulation, was increased in TIL samples in patients with OVC and CRLM. Both TIL populations also contained a significantly higher proportion of activated CD8 + T cells (HLA-DR + /CD38 + ) compared to PBL (CRLM: 30.2% vs 7.7%, (p = 0.0012), OVC: 57.1% vs 12.0%, (p <0.0001)). Conclusion: This study demonstrates that multi-color flow cytometry of freshly digested tumor samples reveals phenotypic differences in TIL vs PBL T cell sub-populations. The TIL composition in primary and metastatic tumors from two distinct histologies were remarkably similar, showing a greater proportion of activated/suppressive Treg (HLA-DR +, CD39 +, CTLA-4 + and Helios + ) and activated cytotoxic T cells (CD8 + /HLA-DR + /CD38 + ) when compared to PBL and an increase in IL-6 mRNA from CD4 TIL.